Construction of databases: advances and significance in clinical research - LongErping; HuangBingjie; WangLiming; LinXiaoyu; LinHaotian (眼科学报, 2015)
Widely used in clinical research, the database is a new type of data management automation technology and the most efficient tool for data management. In this article, we first explain some basic concepts, such as the definition, classification, and establishment of databases. Afterward, the workflow for establishing databases, inputting data, verifying data, and managing databases is presented. Meanwhile, by discussing the application of databases in clinical research, we illuminate the important role of databases in clinical research practice. Lastly, we introduce the reanalysis of randomized controlled trials (RCTs) and cloud computing techniques, showing the most recent advancements of databases in clinical research.